Analisis Perbandingan Kinerja Keuangan Metode Economic Value Added (EVA) dan Metode Rasio Rentabilitas pada PT BPR BKK Kab. Tegal (Perseroda) - Liza Ananda Lestari; Kamal, Bahri; Hasan, Imam (Universitas 45 Surabaya, 2025)
Financial performance is a tool to analyze how a company runs well to be able to get maximum profit. The purpose of this study is to compare the financial performance of companies that apply the Rentability Ratio Method by considering Return on Asset (ROA), BOPO (Operating Cost of Operating Income), Net Interest Margin (NIM), and Economic Value Added (EVA). Quantitative descriptive research is used. In this research, the data collection method is a documentation study, namely the financial statements published by PT BPR BKK KAB TEGAL (Perseroda), and secondary data is used. The results showed that PT BPR BKK KAB TEGAL (Perseroda) has excellent financial performance. Judging from ROA, the company is in a very healthy category with an average of 2.2%, judging from BOPO, the company is in a very healthy category with an average of 83.66%, and judging from NIM, the company is in a very healthy category with an average of 9.18%. Because EVA is negative with an average of Rp. -3,000,901, the company does not experience economic added value. The results of the comparison between ROA, BOPO, NIM, and EVA show that the company should use the EVA method to take into account financial performance with elements of the cost of equity and provide a detailed explanation of the company's added value.